2013
DOI: 10.1021/jp404820k
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Chemically Inhomogeneous, Nanostructured, Si–O Buried Interfaces and Their Effect on the Efficiency of Carbon Nanotube/Si Photovoltaic Heterojunctions

Abstract: An angle resolved X-ray photoemission study of carbon nanotube/ silicon hybrid photovoltaic (PV) cells is reported, providing a direct probe of a chemically inhomogeneous, Si−O buried interface between the carbon nanotube (CNT) networked layer and the n-type Si substrate. By changing the photoelectron takeoff angle of the analyzer, a nondestructive in-depth profiling of a CNT/SiO x / SiO 2 /Si complex interface is achieved. Data are interpreted on the basis of an extensive modeling of the photoemission process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 35 publications
4
42
1
Order By: Relevance
“…Similar results, have been recently confirmed by Pintossi et al (2013), who performed a detailed X-ray photoelectron spectroscopy (XPS) study of the CNT/Si junction before and as a function of time from a HF vapor etching. In addition, Jia et al (2012) also showed that with oxidation increasing, consistently decrease the values of the reverse current density, J 0 , (Fig.…”
Section: The Presence Of Sio 2 Thin Film At Cnt/si Interface and The supporting
confidence: 80%
See 1 more Smart Citation
“…Similar results, have been recently confirmed by Pintossi et al (2013), who performed a detailed X-ray photoelectron spectroscopy (XPS) study of the CNT/Si junction before and as a function of time from a HF vapor etching. In addition, Jia et al (2012) also showed that with oxidation increasing, consistently decrease the values of the reverse current density, J 0 , (Fig.…”
Section: The Presence Of Sio 2 Thin Film At Cnt/si Interface and The supporting
confidence: 80%
“…However, it is worth noting that tunneling transport can be found also in thin layer p-n heterojunctions (Riben and Feucht 1966, Zeidenbergs and Anderson 1967, Anderson 1962) and, in particular, it has been found to play an important role in a p-type SWCNT/n-GaAs heterojunction (Liang and Roth 2008), thus pointing out that this kind of transport mechanism is not a peculiarity of MIS junctions. Besides, the beneficial effects on V OC , J SC and FF of a suitably thin SiO 2 film have been recently reported by Pintossi et al (2013) device is well more complex than expected and needs more sophisticated approaches to be understood. This was evidenced by Wadhwa et al (2010) who suggested a method of improving the solar cell FF and V OC through electronic junction control of the device by using a gate potential applied to the heterojunction via an ionic liquid electrolyte (Fig.…”
Section: The Presence Of Sio 2 Thin Film At Cnt/si Interface and The mentioning
confidence: 99%
“…This suggests that the thinner CNT layer of Cell 15 (25 nm) could favour the effects that determine the variation of electrical parameters across the junction, while in Cell 55 these effects are weakened by the relatively thicker CNT layer (45 nm). Indeed, the dependence of the cell PCE on the CNT layer thickness shows a well-defined behaviour13575859. PCE increases with thickness up to an optimal value (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility to access the buried interface layer by angle resolved X-ray photoemission spectroscopy (AR-XPS) has recently been demonstrated (Fig. 10.10d) and the existence of an oxide layer with optimal thickness was inferred by several groups [32,33,38] to rationalize the behavior of the cells in the presence or absence of oxides. Therefore, in spite of a seemingly straightforward preparation route, the CNT/SiO x /Si interface represents a quite complex system from the point of view of materials, as it matches a relatively low-density CNT bundle layer with a nanostructured and chemically inhomogeneous SiO x layer grown on a n-doped silicon wafer.…”
Section: Cnts For Photovoltaic Applicationsmentioning
confidence: 99%
“…In particular, in devices based on bundles of randomly aligned SWCNT the presence of a thin layer of oxides has always lead to better cell performances [32,33,38].…”
Section: Cnts For Photovoltaic Applicationsmentioning
confidence: 99%